1995
DOI: 10.1164/ajrccm.152.2.7633735
|View full text |Cite
|
Sign up to set email alerts
|

Active expiratory glottic closure during permeability pulmonary edema in nonsedated lambs.

Abstract: It has long been claimed that the active expiratory glottic closure observed in newborns, especially during hyaline membrane disease, is related to hypoxia. However, we recently showed that hypoxia does not lead to active expiratory glottic closure in nonsedated lambs. In this study, we test the hypothesis that glottic closure is related to an excess of lung water present at birth. We studied 17 nonsedated lambs after inducing a permeability pulmonary edema via intravenous of either oleic acid (8 lambs) or hal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
26
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…This study also shows for the first time that PGE 2 enhances expiratory TAEMG activity, thereby resulting in AF braking during expiration. Expiratory TAEMG activity in awake lambs is tonically inhibited by vagal afferents (39), but this activity can also be enhanced by vagal afferents in response to pulmonary deflation (17) or pulmonary edema (40). In the current study, the effect on TAEMG activity was greater during intracarotid than intrajugular infusion, and the augmentation of activity occurred within seconds after starting intracarotid infusion and thus before arterial blood gas tensions could change or significant edema could develop.…”
Section: Discussionmentioning
confidence: 45%
“…This study also shows for the first time that PGE 2 enhances expiratory TAEMG activity, thereby resulting in AF braking during expiration. Expiratory TAEMG activity in awake lambs is tonically inhibited by vagal afferents (39), but this activity can also be enhanced by vagal afferents in response to pulmonary deflation (17) or pulmonary edema (40). In the current study, the effect on TAEMG activity was greater during intracarotid than intrajugular infusion, and the augmentation of activity occurred within seconds after starting intracarotid infusion and thus before arterial blood gas tensions could change or significant edema could develop.…”
Section: Discussionmentioning
confidence: 45%
“…Therefore using diaphragmatic contraction to trigger NIPPV pressure rise does not guarantee an open glottis. In addition, newborn infants and animals commonly have laryngeal abduction during expiratory braking31 and central apnoeas32 to preserve lung volume and protect against desaturation. This would limit the effects of NIPPV by preventing the applied pressures reaching the chest.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data have established that glottal constrictor muscles (e.g., TA muscles) are normally active during the postinspiratory phase of the breathing cycle. This serves to brake expiratory flow and delay lung emptying, a strategy especially used by the newborn in case of lung disease (14). A few studies, however, have reported that TA muscles can, at times, be active in inspiration.…”
Section: Increase In Ta Muscle Inspiratory Emg Activitymentioning
confidence: 99%